The complete mitochondrial genome of Cynops cyanurus cyanurus (Caudata: Salamandridae) and its phylogenetics analysis. Issue 1 (2nd January 2020) - Li, Hao; Cui, Lin; Li, Diyan; Fan, Xiaolan; Yang, Mingyao; Yang, Deying; Ni, Qingyong; Li, Yan; Yao, Yongfang; Xu, Huailiang; Zeng, Bo; Li, Ying; et al.
Abstract: The complete mitochondrial of Cynops cyanurus cyanurus was determined by using Sanger sequencing and the mitogenome size of C. c. cyanurus was 16, 465 bp. It contained 13 protein-coding genes, 22 tRNAs, 2 rRNAs, 1 control region (D-loop) and a non-coding region (NC). In addition, the phylogenetic tree shows that C. c. cyanurus has the closest relationship with C. c. chuxiongensis . Hoping this study can improve our understanding of the species evolutionary relationship of Cynops.